Development of Halal certification requirement model for food industry - A. Manaf, Aini Masmira (2020)
In line with increasing Halal food market demand in Malaysia, Halal certification plays a key role in food and beverages industry specifically in small medium enterprise (SME). From previous studies, the practice of Halal standards is found synonymous with quality certification such as quality management system (QMS) and food safety management system (FSMS). However, the awareness towards the Halal certification and quality systems among SME are at low level. This has led to a low business performance. The aim of this study was to develop QMS-FSMS model in order to help microenterprise entrepreneurs to acquire Halal certification effortlessly. By merging the affected elements which influenced the Halal certification process, it would expedite the process of Halal application yet maintaining product quality. However, no studies which combined QMS-FSMS requirements into Halal certification were conducted in food and beverage microenterprises in Malaysia. Therefore, this was found to be filled as the gap of this study. Semi-structured face-to-face interviews, observation and focus group discussion were used to collect qualitative data. Through purposive sampling and grounded theory approach, twelve microenterprises from Selangor and Pahang were selected as a sample for this study. From data coding analysis, six critical elements, which are top management responsibilities, operation management, team encouragement, quality culture and customer focus were generated. This model was tested with two respective microenterprises in final phase of this study. The result showed that SME 30 has fulfilled 99% of the checklist and has successfully submitted E-Halal application on the same day, meanwhile SME26 only obtained 63.4% and unable to proceed with the E-Halal application. This finding shows that QMS and FSMS implementation could expedite the Halal certification process related to document preparation. This study has revealed entrepreneurs’ knowledge and experience towards QMS, FSMS and Halal certification are very low. Lack of exposure, management skill and proper training in quality system and Halal certification among the owners were the major barriers that lead to difficulty of getting Halal certification especially related to documentation.